Analisis Asuransi Dan Penjaminan Pada Pelaksanaan Pembiayaan iB Serbaguna Di PT Bank Sumut Unit Usaha Syariah - Nur Widya Ningsih; Rahmi Syahriza (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
This article aims to analyze the insurance and guarantee mechanisms in the implementation of iB Serbaguna financing at PT Bank Sumut Sharia Business Unit. The research method used is a descriptive qualitative approach, gathering data through interviews, observations, and related document studies. The results indicate that the application of insurance and guarantees in iB Serbaguna financing is conducted to reduce credit risk and ensure the continuity of customer payments. The insurance used includes life insurance and loss insurance, while the guarantees involve guarantee institutions to enhance confidence in the customers' repayment abilities. This implementation has proven effective in minimizing financing risks and increasing customer trust in the offered Sharia banking products.